Reading social research studies in inequality and deviance - Dixon, Jeffrey C.; Singleton, Royce A. (Thousand Oaks, California SAGE Publications, 2013)
A collection of 20 studies, carefully chosen to represent a broad range of approaches and methods of contemporary social research. Selected journal articles and book excerpts illustrate the relationship between theory and research, the ethical and political dimensions of research, methods of selecting cases and measuring concepts, and various ways of gathering and analyzing data. Organized in 10 units, each unit introduces the methodological topic, provides Web resources related to the topic, presents two reading selections, and then poses questions to assess students' understanding of the researchers' methodology. Focusing on issues of race/ethnicity, gender, class, and crime and deviance, the readings expose students to substantive topics fundamental to, and at the forefront of, the social sciences. In addition, the readings provide examples of both qualitative and quantitative social research; are rigorous applications of methodological concepts; and are abridged carefully to make them accessible to students."--Publisher's website
Keywords: Social sciences -- Research; Research -- Evaluation